The Qur’an and Modern Science: Observations on Methodology (American Journal of Islam and Society, 1991)
IntroductionAnyone who reads the Qur’an carefully and endeavors to attain a properunderstanding of its attitude towads science will face a great number of iiyiitwhich cover science in all its aspects. These fall into four categories: 1) mattersrelated to the reality, horizons, and aims of science or, to put it more precisely,the “philosophy of science and theory of knowledge,” 2) the methodologyof discovering scientific facts, 3) the laws that apply in the various fieldsof science-particularly natural sciences -called the pure sciences, and 4)those laws discovered through experimental methodology and meant to beapplied by a person in hidher capacity as vicegerent of Allah (SWT) onearth, who has been entrusted with the task of creating a higher and betterlife and a finer world. This field is known as the applied sciences.There is undoubtedly a very close relationship between each of thesecategories. Philosophy analyzes the aims of science while methodologyprovides a modus operdndi for discovering facts; that is, it explains the lawsand systems which control the cosmos, the world and life, and which protecttheir movements in time. In turn, these laws and systems furnish humanitywith the formulae which enable individuals to explore the wondrous structureofcreation. Consequently, these laws and systems become the means by whichhumanity can achieve the progress and development of human civilization.Such knowledge can free humanity from the drudgery of day-to-day earthlyexistence, raise its eyes to the heavens and satisfy those spiritual needs whichdistinguish it from all other creatures. An individual can thus perform moreof the duties required of him/her in hidher capacity as vicegerent, and fulfillhidher role of bringing civilization and development to the world ...